(untitled) (Voice of Teacher, 2023)
Beginning with how women know about the particular condition of having pelvic organ prolapse, this article examines what women do when they know about this medical condition. The paper specifically addresses the customary management of this health problem by women. In the process, it also clarifies how people come to possess this knowledge. It also looks at whether this knowledge is enough to treat the diseases or if they also need to stay away from alternative forms of therapy. While doing so, this article also examines whether women with uterine prolapse have narrower healing pathways that only go in one direction or if there are other options in a plural healing context. The ethnographic data from an anthropological study carried out in Nepal’s middle hills served as the basis for the development of this essay.